Analisis Rasio Keuangan Terhadap Laporan Keuangan Pada Pt Wismilak Inti Makmur Tbk Tahun 2020-2023 - Miradji,, Faradisha Nur Ainy , Moh Afrizal; Azzam Jauhar, Armando Deni Kusuma , Delfridus Marlensa Mite, (Jurnal Mirai Management, 2024)
This study analyzes the financial ratios in the financial statements of PT Wismilak Inti Makmur Tbk during the period 2020-2023. Financial ratios are used to evaluate the company's performance in terms of liquidity, profitability, solvency, and operational efficiency. This topic is interesting because it can provide an understanding of how companies face economic challenges, especially in the COVID-19 pandemic situation that affects various business sectors. This study focuses on the main question, namely How is the financial performance of PT Wismilak Inti Makmur Tbk based on the analysis of financial ratios during the period 2020-2023? This study is novel because it specifically analyzes the impact of the pandemic on the company's financial performance, a topic that has not been discussed in depth. The method used is quantitative descriptive with secondary data in the form of financial reports downloaded from the official website of the Indonesia Stock Exchange (www.idx.co.id). The results of the study show that PT Wismilak Inti Makmur Tbk is able to maintain good financial performance despite facing global economic challenges. The liquidity ratio shows the company's ability to meet short-term obligations, profitability is relatively stable despite a slight decline in 2020, solvency reflects a healthy capital structure, and operational efficiency is maintained. In conclusion, PT Wismilak Inti Makmur Tbk has successfully demonstrated good financial resilience during the research period, confirming the importance of financial ratio analysis in evaluating company performance amidst economic dynamics.